THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT HOTEL MANINJAU INDAH, AGAM REGENCY WEST SUMATRA - Verawati Caniago, Riska; Kurniawati, Rohmah (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study aims to determine: (1) the influence of work discipline on employee performance at Hotel Maninjau Indah, Agam Regency, West Sumatra; (2) the influence of work motivation on employee perfor-mance; and (3) the influence of both work discipline and work motivation on employee performance.The method used in this study is quantitative, with data collection techniques including questionnaires and documentation. The questionnaire used was tested for validity and reliability using SPSS software. The population of this study consisted of 35 employees. After data collection, classical assumption tests were conducted prior to data analysis.The results of the analysis show that the coefficient of determination (R²) is 0.513, indicating that work discipline (X1) and work motivation (X2) contribute 51.3% to employee performance (Y), which falls into the strong category. However, based on the regression results, only work motivation has a significant influence on employee performance, while work discipline does not show a significant effect. These findings indicate that the level of work discipline does not directly determine the quality or quantity of employee performance. Other factors such as work motivation, work environment, leadership, and individual competence may have a more dominant influence on performance